Interdecadal variation of precipitation over Yunnan, China in summer and its possible causes - Dong, Zeyu; Gui, Shu; Yang, Ruowen; Cheng, Jinxin; Yang, Huan; Ma, Ji (Frontiers in Environmental Science, 2023)
This study investigates the interdecadal variability (IDV) of summer precipitation in Yunnan during 1961-2019 and its association with the Indo-Pacific Sea surface temperature (SST) configuration based on gauge observation and reanalysis data. The dominant mode of summer precipitation IDV in Yunnan shows a uniform pattern characterizing the alternations of flood and drought. Specifically, a relatively wet period persists from the early 1990s to the early 2000s, followed by a relatively dry period from the early 2000s to the late 2010s. The IDV of precipitation is consistent with the IDV of the column-integrated water vapor flux divergence, where the wind anomalies play a major role in modulating the moisture supply. The main SST forcings of the IDV of precipitation include the sea surface temperature anomalies (SSTAs) over the Bay of Bengal (BOB), the Western Pacific Warm Pool (WPWP), and the western North Pacific (WNP). The negative SSTAs over the BOB and the WPWP trigger a Gill-Matsuno-type response that enhances the cyclonic curvature over Yunnan. The SSTAs over the WNP show a tripole pattern that weakens the WNP subtropical high and further enhances the cyclonic anomaly over Yunnan. The above SST configuration also favors moisture transport to Yunnan. Numerical experiments verify the key physical processes.